Pengembangan Ekonomi Publik Kawasan Objek Wisata Pantai Muara Indah Desa Ogotion Kecamatan Mepanga Kabupaten Parigi Moutong - Indah Kalvari; ARIE RORONG; VERY LONDA (Sam Ratulangi University, 2023)
ABSRACT This study aims to determine the public economic development of the Muara Indah beach tourist attraction in Ogotion Village, Mepanga District, Parigi Moutong Regency. This study uses a qualitative method. Based on the results of research conducted at the location of the Muara Indah beach tourist object that there is so much potential that can be developed and can attract tourists, but the government has not fully allocated funds for the development of the object so that the public economic conditions of the people in the coastal tourism object area are quite apprehensive. Therefore, the community hopes that the Parigi Moutong Regency Government can maximize the development of existing infrastructure so that the allocation, distribution and stabilization of the economy in the area can develop properly. This study uses data analysis techniques, data reduction, data presentation (display) and the conclusion stage (verification). Keywords: Development, Public Economy, Tourist Attractions